THE INFLUENCE OF THE BUZZ GROUP DISCUSSION LEARNING METHOD ON STUDENT LEARNING OUTCOMES IN THE ENGLISH SUBJECT SDN 69 PALEMBANG - Dian Avendo; Djunaidi Djunaidi; Marleni Marleni (Universitas PGRI Palembang, 2024)
This thesis discusses the influence of the Buzz Group Discussion Learning Method on Student Learning Outcomes in English Subjects at SDN 69 Palembang. This research aims to determine (1) the English learning outcomes of class III students at SD Negeri 69 Palembang (2) to determine the English learning outcomes of students using the buzz group discussion learning method (3) to determine whether there is an influence of the buzz group discussion learning method on the results learning English for class III students. This type of research is Quantitative research with Pre-experimental design in the form of One Group Pretest-Posttest design, the subjects of this research are class IIII students at SD Negeri 69 Palembang, the sample is class III as the experimental class, and class III as the control class. Based on the results of descriptive data analysis, the average score for the two groups was obtained, namely the control class (pretest) at 41.25, while the results for the experimental class (posttest) were 67. Meanwhile, based on the results of the t-test calculations, it was found that the tcount value was 8, 02 while ttable with df 38 with a level of 0.05 then ttable = 2.75. So it is stated that tcount > ttable = 8.02 > 2.75 so that tcount is declared significant where Ho is rejected and Ha is accepted. Thus, the hypothesis states that there is an influence of the buzz group discussion learning method on the English learning outcomes of class III students at SD Negeri 69 Palembang.